5G dual-band slotted SIW array antenna. Issue 1 (1st January 2021) - Kumawat, Priyanka; Joshi, Sunil
Abstract : A dual-band slotted substrate-integrated waveguide four-element array antenna for the 5G communication system is presented in this manuscript. Two longitudinal slots are responsible for generating frequency bands of 28 and 38 GHz. The proposed antenna is designed on the substrate duroid 5880/Rogers having a loss tangent and dielectric constant of 0.003 and 2.2, respectively. The developed single-element design at 28 GHz provides 6.35 dBi gain, while at 38 GHz it provides 7.3 dBi gain and the simulation is carried out with CST Microwave Studio, 2018. To accomplish high gain, an optimized four-element array antenna is designed with a parallel feeding network on the same substrate that covers 28 GHz (27.6–28.1 GHz) and 38 GHz band (37.9–38.69 GHz). The designed antenna array attains the radiation efficiency of 88.08% with 12.7 dBi gain at 28 GHz and the efficiency of 84.44% with 15.5 dBi gain at 38 GHz band.